Application of CRISPR/Cas for diagnosis and management of viral diseases of banana - Tripathi, L.; Ntui, V.O.; Tripathi, J.N.; Kumar, P. Lava (Frontiers Media, 2021)
Viral diseases are significant biotic constraints for banana (Musa spp.) production as they affect the yield and limit the international movement of germplasm. Among all the viruses known to infect banana, the banana bunchy top virus and banana streak viruses are widespread and economically damaging. The use of virus-resistant bananas is the most cost-effective option to minimize the negative impacts of viral-diseases on banana production. CRISPR/Cas-based genome editing is emerging as the most powerful tool for developing virus-resistant crop varieties in several crops, including the banana. The availability of a vigorous genetic transformation and regeneration system and a well-annotated whole-genome sequence of banana makes it a compelling candidate for genome editing. A robust CRISPR/Cas9-based genome editing of the banana has recently been established, which can be applied in developing disease-resistant varieties. Recently, the CRISPR system was exploited to detect target gene sequences using Cas9, Cas12, Cas13, and Cas14 enzymes, thereby unveiling the use of this technology for virus diagnosis. This article presents a synopsis of recent advancements and perspectives on the application of CRISPR/Cas-based genome editing for diagnosing and developing resistance against banana viruses and challenges in genome-editing of banana.